Gestión financiera del Cuerpo de Bomberos del Cantón Milagro en el periodo 2023. - Bayas Torres, Patricia Andrea (2025)
The main objective of this project entitled financial management of the Milagro Canton Fire Department in the period 2023 is to analyze the financial management, planning, execution and control of the budget, in order to recognize its sustainability and operational efficiency of the institution. Revenue budget analysis includes review of funds from fees, government subsidies and other contributions. Regarding expenses, both operating and investment costs are examined, ranging from equipment and vehicle maintenance to staff salaries and administrative expenses. Additionally, budget items are evaluated to determine efficiency in the allocation and use of available resources. This analysis seeks to identify possible imbalances and areas where resource allocation can be improved to maximize operational and financial efficiency. The ultimate goal is to provide practical and applicable recommendations that help the Fire Department optimize its financial management, ensuring that resources are used efficiently and effectively, thus improving its response capacity and service to the community. This study is presented as a fundamental tool for strategic decision making and future planning of the institution.